The British possessions in North America from the best authorities - Lewis, Samuel, 1753 or 4-1822 ([Philadelphia], 1794)
Hand coloured. Prime meridians Philadelphia and London. Relief shown pictorially. Bar scale in American miles. Inset: [Labrador, Hudson's Bay, Baffin's Bay, and Greenland]. CNS map no. 172. "Engraved for Carey's American Edition of Guthrie's Geography improved" (top edge).